Cloning and expression of MPT83 gene from Mycobacterium tuberculosis in E. coli BL21 as vaccine candidate of tuberculosis: A preliminary study - Ahmad, Ahyar (J Genet Eng Biotechnol, 2018)
The appearance of Mycobacterium tuberculosis strains leading to drug resistance has caused new problems in TB treatment in various parts of the world and forces WHO to declare TB as a global emergency. With the increase of TB drug resistance, it is convinced that a more effective vaccine development will stop the epidemic of TB. Some M. tuberculosis antigens, one of which is MPT83, have been examined as TB vaccine candidate. MPT83 antigen, which is very immunogenic in lipoprotein micro bacteria, is identified as surface cell interrelated to antigen with cytometry circulation. Having TB resistance from BCG vaccine, MPT83 is considered TB vaccine candidate that can protect people against TB at adult age. The purpose of this research is to conduct amplification of MPT83 antigen cloning, and expression of its antigen on E. coli bacteria. From the result of the research, it is expected that raw material to produce TB vaccine as well as a high-quality antigen can be obtained. The band of DNA in PCR product is 660 bp, while the one in pGEMT-Easy-Mpt83 recombinant plasmid is 3678 bp. This is expressed in E. coli BL21 strain and produces 48 kDa protein as well as GST-MPT83 fusion protein.